2000
DOI: 10.2337/diabetes.49.4.662
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor blockade prevents augmented extracellular matrix component mRNA expression and capillary basement membrane thickening in the retina of diabetic and galactose-fed rats.

Abstract: Endothelins (ETs) are a family of vasoactive peptides that have mitogenic properties and have also been associated with altered long-term nuclear signaling. We have previously shown that mRNA levels for ET-1 , E T-3, and their receptors are upregulated under hyperhexosemic conditions. In this study, an endothelin antagonist was used to assess the effects of endothelin blockage on the production of two basement membrane transcripts, fibronectin and collagen 1 (IV). The microvascular basement membranes were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
103
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 28 publications
6
103
0
1
Order By: Relevance
“…4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats. 4,15 Bosentan treatment also prevented retinal capillary and glomerular basement membrane thickening in these animals. Furthermore, a similar normalization of FN expression by bosentan has been shown in heart tissues of diabetic animals.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats. 4,15 Bosentan treatment also prevented retinal capillary and glomerular basement membrane thickening in these animals. Furthermore, a similar normalization of FN expression by bosentan has been shown in heart tissues of diabetic animals.…”
Section: Discussionmentioning
confidence: 67%
“…[1][2][3][4][5]18 We have previously demonstrated an important role of hyperglycemia-induced ET-1 expression in increased ECM protein deposition. 4,15,18 We have also shown that hyperhexosemia-induced increased FN mRNA expression can be prevented by bosentan treatment in retinas and kidneys of both diabetic and galactose-fed rats. 4,15 Bosentan treatment also prevented retinal capillary and glomerular basement membrane thickening in these animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally recognized that basement membrane thickening is a hallmark of diabetic microvasculopathy, and inappropriate upregulation of the component mRNAs and proteins is thought to be a major factor contributing to this lesion (43)(44)(45). AGEs accumulate on diabetic retinal capillary basement membranes (14) where they are thought to contribute to structural and functional abnormalities on this specialized ECM, including rendering it more resistant to protease modification (46 -48).…”
Section: Discussionmentioning
confidence: 99%
“…*p<0.05 vs control and respective LG; n=4 per treatment [28]. Increased production of ECM proteins, such as fibronectin, may be an important factor leading to the development of long-term changes such as angiogenesis in diabetic retinopathy [3,29]. Several biochemical anomalies induced by high glucose may activate Akt.…”
Section: Discussionmentioning
confidence: 99%